Sulla metodologia storiografica in Italia - Artico, Davide (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
In Italian historiography, methodology may be divided into several separate disciplines, of which research methodology and methodology of historical narration are considered most important. Research methodology comprises, among other things, the procedures of document collecting and the verification of their reliability, and hermeneutical questions about their proper interpretation. A few milestones can be observed in the development of this discipline.
Keywords: Vico, Giambattista (1668-1744); Croce, Benedetto (1866-1952)